1995
DOI: 10.1074/jbc.270.8.3656
|View full text |Cite
|
Sign up to set email alerts
|

The Hemoregulatory Peptide N-Acetyl-Ser-Asp-Lys-Pro Is a Natural and Specific Substrate of the N-terminal Active Site of Human Angiotensin-converting Enzyme

Abstract: Angiotensin I-converting enzyme (ACE) is a zinc-dipeptidyl carboxypeptidase, which contains two similar domains, each possessing a functional active site. Respective involvement of each active site in the degradation of the circulating peptide N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP), a negative regulator of hematopoietic stem cell proliferation, was studied by using wild-type recombinant ACE and two full-length mutants containing a single functional site. Both the N- and C-active sites of ACE exhibit di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
256
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(269 citation statements)
references
References 33 publications
5
256
0
8
Order By: Relevance
“…In contrast, sACE contains another catalytic center in its unique amino-terminal domain (8,19). Although both domains of sACE contain the same zinc-binding motif (His-Glu-X-Y-His), the amino-terminal active site cleaves LHRH 30 times faster and the hematopoietic peptide NH 2 -acetyl-Ser-Gly-Lys-Pro 40 times faster than the carboxyl-terminal active site (18,22). Similar substrate preferences were observed for the AnCE and Acer proteins (12,23).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In contrast, sACE contains another catalytic center in its unique amino-terminal domain (8,19). Although both domains of sACE contain the same zinc-binding motif (His-Glu-X-Y-His), the amino-terminal active site cleaves LHRH 30 times faster and the hematopoietic peptide NH 2 -acetyl-Ser-Gly-Lys-Pro 40 times faster than the carboxyl-terminal active site (18,22). Similar substrate preferences were observed for the AnCE and Acer proteins (12,23).…”
supporting
confidence: 56%
“…Thus, the carboxyl-terminal active center is completely conserved between the two proteins, and in vitro, they cleave many substrates, including angiotensin I, with equal efficiency (6,20). In contrast, several studies have indicated that the amino-terminal active center, present only in sACE, has enzymatic properties that are distinct from those of the shared active center (22). Therefore, it is conceivable that, in vivo, the two active centers are designed to act upon two sets of different substrates, both isozymes cleaving a common set of peptides and only sACE cleaving a second set.…”
Section: Discussionmentioning
confidence: 97%
“…At least three physiologically important peptides are hydrolyzed preferentially or exclusively by the N-domain: luteinizing hormone releasing hormone, Ang 1-7 and AcSDKP (acetyl-Ser-AspLys-Pro). [193][194][195] There is increasing evidence that ACE is the principal metabolizing enzyme for AcSDKP, a natural hemoregulatory hormone. 196 AcSDKP has antiproliferative and antifibrotic activities, and it protects hematopoietic stem cells against chemotherapy-induced injury 196 and limits cardiac fibrosis.…”
Section: Future Of Aceismentioning
confidence: 99%
“…The enzyme plays an important role in blood pressure regulation by converting the inactive decapeptide angiotensin I to the potent vasopressor angiotensin II (Skeggs et al 1956) and inactivating the vasodilator bradykinin (Yang et al 1970). The enzyme is also able to hydrolyze other naturally occurring peptides, such as N-Acetyl-Seryl-Aspartyl-Lysyl-Proline (Rousseau et al 1995), substance P (Skidgel et al 1984) and luteinizing hormone-releasing hormone ( Skidgel and Erdos 1985). ACE is expressed as a somatic isoform (150-180 kDa) in endothelial, epithelial and neuroepithelial cells and as a smaller isoform (90-110 kDa) only in germinal cells in the testes.…”
Section: Introductionmentioning
confidence: 99%
“…The C-and N-domains of ACE are functional and share a high degree of homology, particularly at the active centers, but they differ in substrate specificities, inhibitor and chloride profiles (Wei et al 1991(Wei et al , 1992. The active sites of both domains cleave angiotensin I, substance P and bradykinin with similar efficiency (Jaspard et al 1993) while the natural circulating tetrapeptide N -Acetyl-Seryl-Aspartyl-Lysyl-Proline (Rousseau et al 1995) is a specific substrate for the Ndomain catalytic site.…”
Section: Introductionmentioning
confidence: 99%